Three new species of Tracholena Common, 1965 (Lepidoptera: Tortricidae: Tortricinae: Schoenotenini) from New Caledonia associated with Araucariaceae - Dugdale, John S. (Zootaxa, 2005)
The genus Tracholena (Lepidoptera: Tortricidae: Tortricinae: Schoenotenini) is newly reported from New Caledonia, with three species described as new: T. liparodes, T. nigrilinea, and T.paniense. T. nigrilinea has been reared from male cones of two species of Araucaria at three sites, and the other two are known only from adults caught at light in an Agathis montana forest at 1380m. Apomorphies supporting monophyly of the genus are discussed. An updated checklist is provided and one species, T. indicata Diakonoff, is excluded from Tracholena.